Implicit racial bias across the law - Levinson, Justin D. (Justin David), 1974-; Smith, Roger J. (Roger John), 1948- (Cambridge University Press, 2012)
This book explores how scientific evidence on the human mind might help to explain why racial equality is so elusive.